Initiating and sustaining water sector reforms a synthesis - World Bank (New Delhi Allied, 1999)
This report is the synthesis of a sector wide program undertaken in patnership between the government of India and the world Bank Report preparation was by Christiva wood in association with Keithoblitas.The report synthesizes five specialist reprots on I
Keywords: Water supply-India; Water resources development-Government policy-India